Identification of unusual oxysterols biosynthesised in human pregnancy by charge-tagging and liquid chromatography - mass spectrometry - Dickson, Alison L.; Yutuc, Eylan; Thornton, Catherine A.; Wang, Yuqin; Griffiths, William J. (Frontiers in Endocrinology, 2022)
The aim of this study was to identify oxysterols and any down-stream metabolites in placenta, umbilical cord blood plasma, maternal plasma and amniotic fluid to enhance our knowledge of the involvement of these molecules in pregnancy. We confirm the identification of 20S-hydroxycholesterol in human placenta, previously reported in a single publication, and propose a pathway from 22R-hydroxycholesterol to a C27 bile acid of probable structure 3β,20R,22R-trihydroxycholest-5-en-(25R)26-oic acid. The pathway is evident not only in placenta, but pathway intermediates are also found in umbilical cord plasma, maternal plasma and amniotic fluid but not non-pregnant women.